(untitled) (Epidemiology, Biostatistics, and Public Health, 2023)
Autism spectrum disorder (ASD) is a neurodevelopment disorder characterised by a range of deficits in two specific domains: social communication and social interaction and repetitive patterns of behaviour. Several studies have explored the link between ASD and STEM (science, technology, engineering and mathematics, or other mathematics-grounded disciplines), but results are still uncertain. Objective of the study was to estimate the potential role of systemising abilities in parents as a risk factor for ASD in the offspring, using the achievement of a degree in STEM disciplines as a proxy characteristic of the exposure. There were 1,316 participants overall. There were 658 incident consecutive cases of definite ASD, diagnosed in a Reference Centre for ASD in Italy, from 2001 to 2020. The main exposure variable was parental education level. The risk of ASD in the offspring associated with the main exposure variable and the exposure covariates (e.g. use of neurotropic drugs during the first trimester of the mother’s pregnancy, perinatal outcomes of participants and/or preterm birth) was studied by using conditional logistic regression analysis. In addition, we carried out a mediation analysis to investigate whether and the extent to which covariates significantly associated with ASD risk mediate the relationship between parental education level and ASD in offspring. A STEM degree in parents was significantly associated with risk of ASD in offspring (OR 1.43, 95% CI 1.03-2.54). Familiarity was weakly associated with the risk of ASD (OR 1.33, 95% CI 1.00-1.66) and is the stronger mediator (PME 28%). Sensitivity analysis did not show deviations related to gender or ASD level. Our study moves in the direction of confirming the risk of occurrence of ASD in the offspring of parents with elevated systemising abilities.